High intake of persistent organic pollutants generated by a municipal waste incinerator by breastfed infants. (July 2019) - Xu, Peiwei; Wu, Lizhi; Chen, Yuan; Xu, Dandan; Wang, Xiaofeng; Shen, Haitao; Han, Jianlong; Fu, Qiuli; Chen, Zhijian; Lou, Xiaoming
Abstract: To monitor the body burden of persistent organic pollutants in mothers and infants living in proximity to a 10-year-old municipal waste incinerator (MWI), levels of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) and polychlorinated biphenyls (PCBs) in the breast milk of mothers were evaluated, and the estimated daily intake (EDI) level of these pollutants in infants was assessed. In total, 14 mothers from the exposure area and 18 mothers from a control area were recruited for this study. In addition, the levels of 17 PCDD/F congeners and 18 PCB congeners in the breast milk of the mothers were estimated, and risk assessment for their infants by calculating their EDI levels was performed. The mean levels of ΣPCDD/Fs and TEQ-ΣPCDD/Fs in the breast milk of the exposure group were significantly greater than those of the control group (3.36 vs. 1.47 pg/g wet weight; and 0.24 vs. 0.12 pg TEQ/g wet weight, respectively; p  < 0.05). With respect to PCBs, the mean levels of the total PCBs (ΣPCBs) and non-dioxin like-PCBs (ΣNDL-PCBs) in the exposure group were significantly greater than those in the control group (269 vs. 141 pg/g wet weight; 230 vs. 115 pg/g wet weight, respectively; p  < 0.05). The mean levels of ΣPCDD/Fs and TEQ-ΣPCDD/Fs were positively correlated with the inhabit time of the exposure group (r = 0.636, r = 0.629, p  < 0.05, respectively). The mean EDI level of the exposure group in infants was significantly greater than that of the control group (22.0 vs. 13.0 pg TEQ/kg bw day; p  < 0.05). In conclusion, mothers and their breast-fed infants living in proximity to the 10-year-old MWI located in the Zhejiang Province of China exhibited a significantly higher body burden of PCDD/Fs and PCBs compared to those living in the control area. Graphical abstract: Image 1 Highlights: Mothers residing near a MWI exhibited a higher body burden of PCDD/Fs and PCBs. Levels of PCDD/Fs in the breast milk of mothers were positively correlated with the inhabit time. The infants' EDI of the pollutants was higher in the exposure area compared to the control area. Abstract : Mothers and their breast-fed infants residing near a municipal waste incinerator exhibited a higher body burden of PCDD/Fs and PCBs compared to those residing in the control area.